Polyimide film, polyamic acid, varnish containing the same, polyimide laminate, and method for producing the same

By polymerizing tetracarboxylic dianhydride and diamine components in a specific proportion, a polyimide film is prepared and imidized at low temperatures, which solves the problem of high polyimide film formation temperature and insufficient transparency. The effect of high-efficiency film formation and hot pressing at low temperatures is achieved.

CN114466745BActive Publication Date: 2024-12-17MITSUI CHEMICALS INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202080069159.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-10-03
Filing Date
2020-04-06
Publication Date
2024-12-17
Estimated Expiration
2040-04-06

AI Technical Summary

Technical Problem

The existing polyimides require high temperatures during film formation, which leads to an impact on the coated object, and lacks transparency and chemical resistance, making it difficult to effectively form and bond at low temperatures.

Method used

Polyimide films are prepared by polymers of tetracarboxylic acid dianhydride and diamine components in a specific proportion, and imidized at a lower temperature to form polyimide Imide laminate.

Benefits of technology

The film formation and hot pressing of polyimide films are achieved at lower temperatures (such as around 250℃), which maintains high transparency and good chemical resistance, and is suitable for the bonding and protection of various components. layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003574256930000021
    Figure BDA0003574256930000021
  • Figure BDA0003574256930000031
    Figure BDA0003574256930000031
  • Figure BDA0003574256930000041
    Figure BDA0003574256930000041
Patent Text Reader

Abstract

The object of the present invention is to provide a polyimide film which can be formed at a relatively low temperature, has little coloration and high transparency, and a polyamic acid or varnish for obtaining the polyimide film. The polyimide film comprises a polyimide which is a polymer of a tetracarboxylic dianhydride component and a diamine component. The tetracarboxylic dianhydride component comprises 60 mol% to 100 mol% of a tetracarboxylic dianhydride of a specific structure relative to the total amount of the tetracarboxylic dianhydride, and the diamine component comprises 30 mol% to 70 mol% of an alicyclic diamine and 30 mol% to 70 mol% of an alkylenediamine relative to the total amount of the diamine component.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polyimide film, a polyamic acid and a varnish containing the same, and a polyimide laminate and a method for producing the same. Background Art

[0002] In the past, epoxy resins and acrylic resins were well known as colorless and transparent coating resins or adhesive resins. However, these resins have problems in terms of heat resistance and chemical resistance. On the other hand, polyimide has excellent heat resistance or chemical resistance, mechanical properties, electrical properties, etc. However, the film forming temperature of existing polyimide is about 300°C. If such polyimide is to be applied and film formed, there is a problem that the coated object (for example, substrate, etc.) cannot withstand the film forming temperature.

[0003] In recent years, polyimide, which can be formed at relatively low temperatures, has been studied as a coating film for magnetic bodies, a binder for inorganic substances or metal particles, etc. Among them, colorless and transparent polyimide is expected to be applied to various fields in terms of design and ease of coloring with pigments.

[0004] Various polyimides have been proposed so far. For example, Patent Document 1 proposes a thermoplastic polyimide obtained from a specific alicyclic diamine and an aromatic tetracarboxylic dianhydride. Patent Document 2 proposes a varnish of a polyimide obtained from a specific alicyclic acid dianhydride and an aromatic diamine.

[0005] [Prior art literature]

[0006] [Patent Document]

[0007] Patent Document 1: Japanese Patent No. 5365762

[0008] Patent Document 2: International Publication No. 2008 / 004615 Summary of the invention

[0009] Technical problem to be solved by the invention

[0010] As mentioned above, general polyimide has a high glass transition temperature. Therefore, when such polyimide is applied and film-formed, it must be heated to a high temperature, which easily affects the coated object (e.g., substrate, etc.). Therefore, research is being conducted to reduce the glass transition temperature of polyimide to reduce the film-forming temperature.

[0011] However, if the glass transition temperature of polyimide is reduced, the decomposition starting temperature is easily reduced, or the transparency of the film obtained is easily reduced. In addition, about existing polyimide, the fluidity of polyamic acid or its varnish as precursor is low, and it is difficult to carry out film formation, or it is difficult to obtain uniform polyimide. And then, it is difficult to carry out thermocompression bonding.

[0012] On the other hand, the polyimide of Patent Document 2 can be dissolved in a solvent to form a varnish. However, such a polyimide has low chemical resistance, and there is a problem that the use of the polyimide film is likely to be limited.

[0013] Under the circumstances described above, a polyimide film which can be easily formed, has little coloration, has high transparency, and can be bonded even at a relatively low temperature is desired.

[0014] The present invention is obtained in view of this situation, and its purpose is to provide a polyimide film which can be easily formed, has little coloration, high transparency, and can be bonded even at a relatively low temperature, and a polyamic acid or a varnish containing the polyamic acid for obtaining the polyimide film. In addition, the purpose of the present invention is also to provide a polyimide film or a method for manufacturing the same.

[0015] Methods used to solve problems

[0016] The present invention provides the following polyimide film.

[0017] [1] A polyimide film comprising a polyimide which is a polymer of a tetracarboxylic dianhydride component and a diamine component, wherein the tetracarboxylic dianhydride component comprises 60 mol % to 100 mol % of any one compound selected from the group consisting of the following compounds A to C, based on the total amount of the tetracarboxylic dianhydride, and the diamine component comprises 30 mol % to 70 mol % of an alicyclic diamine and 30 mol % to 70 mol % of an alkylenediamine, based on the total amount of the diamine component;

[0018] Compound A: biphenyltetracarboxylic dianhydride which may have three or less substituents containing an alkyl group having 1 to 4 carbon atoms,

[0019] Compound B: naphthalenetetracarboxylic dianhydride which may have three or less substituents containing an alkyl group having 1 to 4 carbon atoms,

[0020] Compound C: Bisphenyl tetracarboxylic dianhydride which may have three or less substituents including an alkyl group having 1 to 4 carbon atoms and includes any of the following structures:

[0021] [Chemistry 1]

[0022]

[0023]

[0024] [2] A polyimide film comprising a polyimide which is a polymer of a tetracarboxylic dianhydride component and a diamine component, wherein the tetracarboxylic dianhydride component comprises 60 mol% to 100 mol% of biphenyltetracarboxylic dianhydride relative to the total amount of the tetracarboxylic dianhydride, the biphenyltetracarboxylic dianhydride may have three or less substituents comprising an alkyl group having 1 to 4 carbon atoms, and the diamine component comprises 30 mol% to 70 mol% of an alicyclic diamine and 30 mol% to 70 mol% of an alkylenediamine relative to the total amount of the diamine component.

[0025] [3] The polyimide film according to [1] or [2], wherein the alkylene group of the alkylenediamine has 2 to 12 carbon atoms.

[0026] [4] The polyimide film according to any one of [1] to [3], wherein the alicyclic diamine is at least one compound selected from the group consisting of 1,4-diaminomethylcyclohexane, 1,3-diaminomethylcyclohexane, norbornanediamine, cyclohexanediamine, isophoronediamine, and 4,4′-methylenebis(cyclohexylamine).

[0027] [5] The polyimide film according to any one of [1] to [4], wherein the alicyclic diamine includes 1,4-diaminomethylcyclohexane, and the alkylenediamine includes 1,6-hexamethylenediamine.

[0028] [6] The polyimide film according to any one of [1] to [5], wherein the tetracarboxylic dianhydride component contains 40 mol % or less of 4,4′-oxydiphthalic anhydride.

[0029] The present invention provides the following polyamic acid and a polyamic acid varnish containing the same.

[0030] [7] A polyamic acid, which is a polymer of a tetracarboxylic dianhydride component and a diamine component, wherein the tetracarboxylic dianhydride component contains 60 mol% to 100 mol% of any one compound selected from the group consisting of the following compounds A to C, based on the total amount of the tetracarboxylic dianhydride, and the diamine component contains 30 mol% to 70 mol% of an alicyclic diamine and 30 mol% to 70 mol% of an alkylenediamine, based on the total amount of the diamine component;

[0031] Compound A: biphenyltetracarboxylic dianhydride which may have three or less substituents containing an alkyl group having 1 to 4 carbon atoms,

[0032] Compound B: naphthalenetetracarboxylic dianhydride which may have three or less substituents containing an alkyl group having 1 to 4 carbon atoms,

[0033] Compound C: Bisphenyl tetracarboxylic dianhydride which may have three or less substituents including an alkyl group having 1 to 4 carbon atoms and includes any of the following structures:

[0034] [Chemistry 2]

[0035]

[0036] [8] A polyamic acid, which is a polymer of a tetracarboxylic dianhydride component and a diamine component, wherein the tetracarboxylic dianhydride component comprises 60 mol% to 100 mol% of biphenyltetracarboxylic dianhydride relative to the total amount of the tetracarboxylic dianhydride, the biphenyltetracarboxylic dianhydride may have three or less substituents containing an alkyl group having 1 to 4 carbon atoms, and the diamine component comprises 30 mol% to 70 mol% of an alicyclic diamine and 30 mol% to 70 mol% of an alkylene diamine relative to the total amount of the diamine component.

[0037] [9] The polyamic acid according to [7] or [8], wherein the alkylene group of the alkylenediamine has 2 to 12 carbon atoms.

[0038]

[10] The polyamic acid according to any one of [7] to [9], wherein the alicyclic diamine is at least one compound selected from the group consisting of 1,4-diaminomethylcyclohexane, 1,3-diaminomethylcyclohexane, norbornanediamine, cyclohexanediamine, isophoronediamine, and 4,4′-methylenebis(cyclohexylamine).

[0039]

[11] The polyamic acid according to any one of [7] to

[10] , having an intrinsic viscosity (η) of 0.62 dL / g or more.

[0040]

[12] The polyamic acid according to any one of [7] to

[11] , wherein the alicyclic diamine comprises 1,4-diaminomethylcyclohexane, and the alkylene diamine comprises 1,6-hexamethylenediamine.

[0041]

[13] The polyamic acid according to any one of [7] to

[12] , wherein the tetracarboxylic dianhydride component contains 40 mol % or less of 4,4′-oxydiphthalic anhydride.

[0042]

[14] A polyamic acid varnish comprising the polyamic acid according to any one of [7] to

[13] and a solvent.

[0043] The present invention provides the following polyimide laminate and a method for producing the same.

[0044]

[15] A method for manufacturing a polyimide laminate, which is a method for manufacturing a polyimide laminate having a substrate and a polyimide layer laminated thereon, comprising: a step of coating the polyamic acid varnish described in

[14] on the substrate; and a step of heating the coating film of the polyamic acid varnish in an inert gas environment.

[0045]

[16] A method for producing a polyimide laminate, comprising: applying the polyamic acid varnish described in

[14] on the substrate; and heating the coating film of the polyamic acid varnish in an air environment.

[0046]

[17] A polyimide laminate comprising: a substrate; and the polyimide film according to any one of [1] to [6] disposed on the substrate.

[0047] Effects of the Invention

[0048] The polyimide film of the present invention can be formed on various components at a relatively low temperature (e.g., a temperature of about 250° C.), and the polyimide film can be thermally pressed onto other components at a relatively low temperature. Furthermore, the polyimide film has little coloration and high transparency. Therefore, it can be used in coating materials for various components or adhesives for inorganic substances or metal particles. DETAILED DESCRIPTION

[0049] 1. About polyimide film

[0050] The polyimide film of the present invention comprises a specific polyimide which is a polymer of a specific tetracarboxylic dianhydride component and a specific diamine component. More specifically, it comprises a specific polyimide obtained by polymerizing a tetracarboxylic dianhydride component and a diamine component, wherein the tetracarboxylic dianhydride component comprises 60 mol% to 100 mol% of any one tetracarboxylic dianhydride selected from the group consisting of the following compounds A to C, relative to the total amount thereof, and the diamine component comprises 30 mol% to 70 mol% of an alicyclic diamine and 30 mol% to 70 mol% of an alkylenediamine, relative to the total amount thereof.

[0051] Compound A: Biphenyltetracarboxylic dianhydride which may have three or less substituents containing an alkyl group having 1 to 4 carbon atoms

[0052] Compound B: naphthalenetetracarboxylic dianhydride which may have three or less substituents containing an alkyl group having 1 to 4 carbon atoms

[0053] Compound C: Bisphenyl tetracarboxylic dianhydride which may have three or less substituents including an alkyl group having 1 to 4 carbon atoms and includes any of the following structures:

[0054] [Chemistry 3]

[0055]

[0056]

[0057] In addition, within the scope of not damaging the purpose and effect of the present invention, the polyimide film may also include components other than the specific polyimide. Wherein, relative to the gross mass of the polyimide film, the amount of the specific polyimide is preferably 80% by mass or more, more preferably 90% by mass or more, and further preferably substantially all composed of the specific polyimide.

[0058] Hereinafter, this specific polyimide will be described in detail.

[0059] (Tetracarboxylic dianhydride component)

[0060] The tetracarboxylic dianhydride component for preparing the specific polyimide contains 60 mol% to 100 mol% of any one compound selected from the group consisting of the compounds A to C relative to the total amount thereof. In addition, the tetracarboxylic dianhydride component may contain only one of the compounds A to C, or may contain two or more. The content of any one of the compounds A to C is 60 mol% to 100 mol% relative to the total amount of the tetracarboxylic dianhydride component.

[0061] Among the above, the tetracarboxylic dianhydride component preferably contains 60 mol% to 100 mol% of compound A (biphenyltetracarboxylic dianhydride (BPDA, hereinafter also referred to as "biphenyltetracarboxylic dianhydride") which may have three or less substituents containing alkyl groups with carbon numbers of 1 to 4). If the tetracarboxylic dianhydride component contains biphenyltetracarboxylic dianhydride, it is not easy to produce by-products (salts) during the polymerization of polyamic acid, and it is easy to polymerize the diamine component and the tetracarboxylic dianhydride component. In addition, if the amount of biphenyltetracarboxylic dianhydride is within this range, the transparency and thermal compression bonding of the polyimide film also become good. Furthermore, biphenyltetracarboxylic dianhydride is relatively cheap and can reduce the cost of the polyimide film. Relative to the total amount of the tetracarboxylic dianhydride component, the amount of biphenyltetracarboxylic dianhydride is preferably 80 mol% or more, more preferably 85 mol% or more.

[0062] Examples of the compound A (biphenyltetracarboxylic dianhydride) include: 3,3',4,4'-biphenyltetracarboxylic dianhydride which may have three or less substituents containing an alkyl group having 1 to 4 carbon atoms, and 2,2',3,3'-biphenyltetracarboxylic dianhydride which may have three or less substituents containing an alkyl group having 1 to 4 carbon atoms. The carbon number of the alkyl group as a substituent is preferably 1 or 2. In addition, the total number of substituents can be three or less, and the substituents can be bonded to any position (ring) of the biphenyltetracarboxylic dianhydride. In addition, when the biphenyltetracarboxylic dianhydride has two or more substituents, these substituents may be the same group or different groups.

[0063] Among biphenyltetracarboxylic dianhydride, 3,3′,4,4′-biphenyltetracarboxylic dianhydride is particularly preferred in terms of availability and the like.

[0064] When the tetracarboxylic dianhydride component contains compound B (naphthalenetetracarboxylic dianhydride (hereinafter, also referred to as "naphthalenetetracarboxylic dianhydride") which may have three or less substituents containing an alkyl group with a carbon number of 1 to 4), it is not easy to produce by-products (salts) during the polymerization of polyamic acid, and it is easy to polymerize the diamine component and the tetracarboxylic dianhydride component. In addition, if the amount of naphthalenecarboxylic dianhydride in the tetracarboxylic dianhydride component is within the above range, the transparency and thermal compression bonding of the polyimide film also become good. Furthermore, naphthalenetetracarboxylic dianhydride is relatively cheap and can reduce the cost of the polyimide film. The amount of naphthalenetetracarboxylic dianhydride is preferably 80 mol% or more, more preferably 85 mol% or more relative to the total amount of the tetracarboxylic dianhydride component.

[0065] Examples of the compound B (naphthalenetetracarboxylic dianhydride) include: 2,3,6,7-naphthalenetetracarboxylic dianhydride which may have three or less substituents containing an alkyl group having 1 to 4 carbon atoms, and 1,2,5,6-naphthalenetetracarboxylic dianhydride which may have three or less substituents containing an alkyl group having 1 to 4 carbon atoms. The carbon number of the alkyl group as a substituent is preferably 1 or 2. In addition, the total number of substituents can be three or less, and the substituents can be bonded to any position (ring) of naphthalenetetracarboxylic dianhydride. In addition, when naphthalenetetracarboxylic dianhydride has two or more substituents, these substituents may be the same group or different groups.

[0066] When the tetracarboxylic dianhydride component contains compound C (bisphenyl tetracarboxylic dianhydride containing any of the above structures (hereinafter, also referred to as "bisphenyl tetracarboxylic dianhydride")), it is not easy to produce by-products (salts) during the polymerization of polyamic acid, and it is easy to polymerize the diamine component and the tetracarboxylic dianhydride component. In addition, if the amount of bisphenyl tetracarboxylic dianhydride in the tetracarboxylic dianhydride component is within the above range, the transparency and thermal compression bonding of the polyimide film also become good. Furthermore, bisphenyl tetracarboxylic dianhydride is relatively cheap and can reduce the cost of the polyimide film. Relative to the total amount of the tetracarboxylic dianhydride component, the amount of bisphenyl tetracarboxylic dianhydride is preferably 80 mol% or more, more preferably 85 mol% or more.

[0067] Examples of the compound C (bisphenyl tetracarboxylic dianhydride) include bisphenyl tetracarboxylic dianhydrides represented by the following structural formula.

[0068] [Chemistry 4]

[0069]

[0070]

[0071] In addition, the compound may have three or less substituents including an alkyl group having 1 to 4 carbon atoms. Here, the carbon number of the substituent (alkyl group) bonded to the bisphenyl tetracarboxylic dianhydride is preferably 1 or 2. In addition, the total number of substituents may be three or less, and the substituents may be bonded to any position (ring) of the bisphenyl tetracarboxylic dianhydride. In addition, when the bisphenyl tetracarboxylic dianhydride has two or more substituents, these substituents may be the same group or different groups.

[0072] On the other hand, the tetracarboxylic dianhydride component may further include 4,4'-oxydiphthalic anhydride (ODPA). If the tetracarboxylic dianhydride component includes 4,4'-oxydiphthalic anhydride, the glass transition temperature of the polyimide film tends to be lower, and the decomposition starting temperature tends to be higher. Relative to the total amount of the tetracarboxylic dianhydride component, the amount of 4,4'-oxydiphthalic anhydride is preferably 0 mol% to 40 mol%, more preferably 5 mol% to 15 mol%. In addition, 4,4'-oxydiphthalic anhydride (ODPA) may also have three or less substituents containing alkyl groups having 1 to 4 carbon atoms.

[0073] Moreover, the tetracarboxylic dianhydride component may contain tetracarboxylic dianhydrides other than the above-mentioned compounds A to C and 4,4′-oxydiphthalic anhydride, within a range not impairing the object and effect of the present invention.

[0074] Examples of other tetracarboxylic dianhydrides include known tetracarboxylic dianhydrides, and specifically include aromatic tetracarboxylic dianhydrides which may be substituted, alicyclic tetracarboxylic dianhydrides, and the like.

[0075] Moreover, the specific polyimide may contain a part of trianhydride and tetraanhydride instead of the said tetracarboxylic dianhydride component. Examples of acid trianhydrides include hexacarboxylic trianhydride, and examples of acid tetraanhydrides include octacarboxylic tetraanhydrides.

[0076] (Diamine component)

[0077] The diamine component for preparing the specific polyimide contains 30 mol% to 70 mol% of alicyclic diamine and 30 mol% to 70 mol% of alkylenediamine relative to the total amount thereof. The total amount of alicyclic diamine and alkylenediamine is preferably 80 mol% or more, more preferably 90 mol% or more, and preferably all of the alicyclic diamine and alkylenediamine are used.

[0078] The amount of alicyclic diamine is more preferably 35 mol% to 65 mol% relative to the total amount of diamine components, and is further preferably 45 mol% to 55 mol%. On the other hand, the amount of alkylenediamine is more preferably 35 mol% to 65 mol% relative to the total amount of diamine components, and is further preferably 45 mol% to 55 mol%. In addition, the molar ratio of alicyclic diamine to alkylenediamine is 3 / 7 or more and 7 / 3 or less, more preferably 4 / 6 or more and 6 / 4 or less, and further preferably 4.5 / 5.5 or more and 5.5 / 4.5 or less. If the molar ratio of alicyclic diamine to alkylenediamine is within this range, the glass transition temperature and light transmittance of the obtained polyimide film are easily within the desired range.

[0079] The alicyclic diamine may be a compound having an alicyclic structure and two amines, and a substituent may be bonded to the alicyclic structure. Examples of alicyclic diamines include 1,4-diaminomethylcyclohexane (1,4-BAC), 1,3-diaminomethylcyclohexane (1,3-BAC), norbornane diamine (NBDA), cyclohexane diamine (DACH), isophorone diamine, 4,4'-methylenebis(cyclohexylamine), etc. The specific polyimide may contain only one alicyclic diamine or two or more alicyclic diamines.

[0080] Among the above, the alicyclic diamine is preferably 1,4-diaminomethylcyclohexane. In addition, regarding 1,4-diaminomethylcyclohexane, there are geometric isomers including cis-isomers and trans-isomers, and it can be any one of them. Among them, it is particularly preferred that the content ratio of the trans-isomer to the cis-isomer (trans-isomer + cis-isomer = 100%) is more than 60% and less than 100% for the trans-isomer and more than 0% and less than 40% for the cis-isomer. The content ratio of the cis-isomer and the trans-isomer can be calculated by 1 confirmed by H-NMR.

[0081] On the other hand, alkylenediamines can be compounds having an alkylene group and two amines, and a substituent may be bonded to the alkylene group. The carbon number of the alkylene group is preferably 2 to 12. In addition, the alkylene group may be linear or branched, and is preferably linear from the viewpoint that the glass transition temperature of the polyimide film is easily within the desired range. Specific examples of alkylenediamines include 1,6-hexanediamine (HMDA), 1,7-heptanediamine, 1,9-nonanediamine, 1,12-diaminododecane, and the like. A specific polyimide may contain only one alkylenediamine, or may contain two or more.

[0082] In addition, within the scope of not impairing the purpose and effect of the present invention, the diamine component may also include components other than the alicyclic diamine and alkylenediamine. Examples of other diamines include various known diamines, specifically, diamines having an aromatic ring, diamines having a spirobiindane ring, siloxane diamines, ethylene glycol diamines, alkylenediamines, alicyclic diamines, etc.

[0083] (2) Method for producing polyimide film

[0084] The specific polyimide contained in the polyimide film of the present invention can be obtained by polymerizing the diamine component and the tetracarboxylic dianhydride component by a known method. The polyimide may be a random polymer or a block copolymer.

[0085] The polyimide film of the present invention can be obtained by: 1) polymerizing the diamine component and the tetracarboxylic dianhydride component to prepare polyamic acid, 2) applying a polyamic acid varnish containing the polyamic acid on a substrate to form a coating film, and 3) imidizing (ring-closing) the polyamic acid in the coating film.

[0086] In addition, when polyimide is made into a block copolymer, it can be obtained by the following methods: 1) reacting a polyamic acid oligomer and a polyimide oligomer to prepare a block polyamic acid imide, 2) applying a block polyamic acid imide varnish containing the block polyamic acid imide on a substrate to form a coating film, and 3) imidizing (ring-closing) the block polyamic acid imide in the coating film.

[0087] (Preparation of polyamic acid or block polyamic acid imide)

[0088] When the polyimide to be prepared is a random polymer, the tetracarboxylic dianhydride component and the diamine component are mixed and polymerized to obtain polyamic acid. Here, the ratio (y / x) of the total molar amount x of the diamine component and the total molar amount y of the tetracarboxylic dianhydride component when preparing polyamic acid is preferably 0.970 to 1.100, more preferably 0.990 to 1.010, and further preferably 0.995 to 1.005. By setting the amount of the diamine component and the amount of the tetracarboxylic dianhydride component when preparing polyamic acid to the above range, it is easy to set the intrinsic viscosity of the obtained polyamic acid to the desired range.

[0089] The polymerization method of the diamine component and the tetracarboxylic dianhydride component is not particularly limited, and a known method can be used. For example, a container including a stirrer and a nitrogen inlet pipe is prepared, and a solvent is added to the container after nitrogen substitution. Then, the diamine component is added in a manner such that the final solid content concentration of the polyamic acid is less than 50% by mass, and the temperature is adjusted and stirred. A predetermined amount of tetracarboxylic dianhydride is added to the solution. Then, the temperature is adjusted while stirring for about 1 hour to 50 hours.

[0090] Here, the solvent used when preparing the polyamic acid is not particularly limited as long as it can dissolve the diamine component and the tetracarboxylic dianhydride component. For example, an aprotic polar solvent and / or a water-soluble alcohol solvent can be used.

[0091] Examples of aprotic polar solvents include N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, hexamethylphosphoramide, phosphoramide), 1,3-dimethyl-2-imidazolidinone, etc.; as ether compounds, 2-methoxyethanol, 2-ethoxyethanol, 2-(methoxymethoxy)ethoxyethanol, 2-isopropoxyethanol, 2-butoxyethanol, tetrahydrofurfuryl alcohol, diethylene glycol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, triethylene glycol, triethylene glycol monoethyl ether, tetraethylene glycol, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, dipropylene glycol, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, tripropylene glycol monomethyl ether, polyethylene glycol, polypropylene glycol, tetrahydrofuran, dioxane, 1,2-dimethoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, etc.

[0092] Examples of the water-soluble alcohol solvent include methanol, ethanol, 1-propanol, 2-propanol, tert-butanol, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 1,5-pentanediol, 2-butene-1,4-diol, 2-methyl-2,4-pentanediol, 1,2,6-hexanetriol, diacetone alcohol, and the like.

[0093] The solvent used in the preparation of the polyamic acid may contain only one of the above components, or may contain two or more thereof. Among the above, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, or a mixed solution thereof is preferred.

[0094] On the other hand, when the polyimide to be prepared is a block polymer, a specific diamine component and a tetracarboxylic dianhydride component are polymerized to prepare an amine-terminated polyamic acid oligomer and an anhydride-terminated polyimide oligomer in advance. Then, an anhydride-terminated polyimide oligomer solution is added to the amine-terminated polyamic acid oligomer solution and stirred to polymerize them to obtain a block polyamic acid imide.

[0095] Here, in order to obtain a specific polyimide, it is preferred that the intrinsic viscosity (η) of polyamic acid or block polyamic acid imide is set to 0.62dL / g or more. The intrinsic viscosity (η) is preferably 0.80dL / g or more, more preferably 1.00dL / g or more. The intrinsic viscosity (η) of polyamic acid or block polyamic acid imide can be adjusted by the type and amount of the diamine component and the tetracarboxylic dianhydride component when preparing polyamic acid or block polyamic acid imide. In this specification, the intrinsic viscosity (η) is the value obtained by measuring the Ubbelohde viscosity tube at 25 ° C when the concentration of polyamic acid is set to 0.5g / dL. If the intrinsic viscosity (η) of polyamic acid or block polyamic acid imide is 0.62dL / g or more, the thermocompression bonding of the polyimide film obtained is especially easy to become good.

[0096] (Application of varnish)

[0097] A polyamic acid varnish (or a block polyamic acid imide varnish, hereinafter also referred to as "varnish") comprising the polyamic acid (or block polyamic acid imide) and a solvent is applied on the surface of various substrates to form a coating film. The solvent contained in the varnish may be the same as or different from the solvent used in the preparation of the polyamic acid. The varnish may contain only one solvent or two or more solvents.

[0098] Relative to the total amount of varnish, the amount of polyamic acid (or block polyamic acid imide) is preferably 1% by mass to 50% by mass, more preferably 10% by mass to 45% by mass. If the amount of polyamic acid (or block polyamic acid imide) exceeds 50% by mass, the viscosity of varnish is excessively increased, and there is a situation that it is not easy to be coated on substrate. On the other hand, if the concentration of polyamic acid (or block polyamic acid imide) is less than 1% by mass, the viscosity of varnish is too low, and there is a situation that varnish cannot be coated as a desired thickness. In addition, the drying of the solvent takes time, and the manufacturing efficiency variation of polyimide film is poor.

[0099] The viscosity of the varnish is preferably 500 mPa·s to 100,000 mPa·s, more preferably 3,000 mPa·s to 60,000 mPa·s, and even more preferably 4,500 mPa·s to 20,000 mPa·s. When the viscosity is within this range, the varnish is easily applied and a polyimide film of a desired thickness is easily obtained. The above viscosity is measured at 25° C. using an E-type viscometer.

[0100] The substrate to be coated with the varnish is not particularly limited as long as it has solvent resistance and heat resistance. The substrate is preferably a substrate with good releasability of the obtained polyimide layer, preferably a flexible substrate such as glass, a metal or a heat-resistant polymer film. Examples of flexible substrates containing metals include metal foils containing copper, aluminum, stainless steel, iron, silver, palladium, nickel, chromium, molybdenum, tungsten, zirconium, gold, cobalt, titanium, tantalum, zinc, lead, tin, silicon, bismuth, indium or alloys thereof. A release agent may also be applied to the surface of the metal foil.

[0101] On the other hand, examples of the flexible substrate comprising a heat-resistant polymer film include: polyimide film, aromatic polyamide film, polyetheretherketone film, polyetherethersulfone film, etc. The flexible substrate comprising a heat-resistant polymer film may also contain a release agent and an antistatic agent, or may be coated with a release agent and an antistatic agent on the surface. Since the obtained polyimide film has good peelability and high heat resistance and solvent resistance, the substrate is preferably a polyimide film.

[0102] The shape of the substrate can be appropriately selected according to the shape of the polyimide film to be manufactured, and can be a single sheet or a long strip. The thickness of the substrate is preferably 5 μm to 150 μm, more preferably 10 μm to 70 μm. If the thickness of the substrate is less than 5 μm, the substrate may be wrinkled or broken during the application of the varnish.

[0103] The method of applying varnish to the substrate is not particularly limited as long as it is a method that can be applied with a certain thickness. Examples of coating devices include die coaters, notch wheel coaters, roll coaters, gravure coaters, curtain coaters, spray coaters, die lip coaters, etc. The thickness of the coating to be formed can be appropriately selected according to the thickness of the desired polyimide film.

[0104] (Imidization of polyamic acid (or block polyamic acid imide))

[0105] Next, the coating film of the varnish containing polyamic acid (or block polyamic acid imide) is heated, and the polyamic acid (or block polyamic acid imide) is imidized (ring closed). Specifically, while the temperature is raised from a temperature below 150°C to more than 200°C, the coating film of the varnish is heated, and the polyamic acid (or block polyamic acid imide) is imidized. In addition, at this time, the solvent in the coating film is removed. Then, after heating to a predetermined temperature, it is heated at a certain time below 220°C.

[0106] Usually, the temperature at which the polyamic acid is imidized is 150°C to 220°C. Therefore, if the temperature of the coating is rapidly increased to above 220°C, the polyamic acid on the surface of the coating is imidized before the solvent evaporates from the coating. As a result, the solvent remaining in the coating produces bubbles or causes the surface of the coating to be concave and convex. Therefore, it is preferred that the temperature of the coating is slowly increased within a temperature range of 150°C to 220°C. Specifically, it is preferred that the heating rate in the temperature range of 150°C to 220°C is set to 0.25°C / min to 50°C / min, more preferably to 1°C / min to 40°C / min, and further preferably to 2°C / min to 30°C / min.

[0107] The temperature rise may be continuous or stepwise. If the temperature rise is continuous, the obtained polyimide film is less likely to have a poor appearance. In addition, the temperature rise rate may be constant or may be changed in the middle of the temperature rise.

[0108] An example of a method for heating a single-sheet coating while increasing the temperature is to increase the temperature in an oven. In this case, the heating rate is adjusted by the setting of the oven. In addition, in the case of heating a long strip of coating while increasing the temperature, for example, a plurality of heating furnaces for heating the coating are arranged along the conveying (moving) direction of the substrate, and the temperature of each heating furnace is changed. For example, the temperature of each heating furnace can be increased along the moving direction of the substrate. In this case, the heating rate is adjusted by the conveying speed of the substrate.

[0109] As mentioned above, after heating, it is preferably heated at a temperature below 220°C for a certain period of time so that the residual solvent amount in the polyimide film is less than 1% by mass. In order to reduce the residual solvent amount in the film, general polyimide needs to be heated to more than 280°C. However, according to the above-mentioned specific polyimide, the glass transition temperature can be set to 180°C to 220°C. Therefore, even by heating below 220°C, the residual solvent amount can be less than 1% by mass. In addition, it is more preferred to make the solvent amount in the film less than 0.5% by mass. The residual solvent amount can be measured using a thermal decomposition device using a gas chromatograph GC-1700 manufactured by Shimadzu Corporation. In addition, the heating time is usually about 0.5 hours to 2 hours.

[0110] The heating method for heating the coating film at 220° C. or less is not particularly limited, and for example, heating can be performed in an oven adjusted to a constant temperature. Alternatively, a long coating film can be heated in a heating furnace maintained at a constant temperature.

[0111] Here, even if general polyimide is heated at 200° C., desolvation and imidization do not proceed sufficiently. However, since the Tg of the polyimide of the present invention is about 200° C., heating at 220° C. or lower is sufficient, and coloration is also less.

[0112] On the other hand, if the heating environment is set to an inert gas environment, the coloring of the polyimide film is further reduced, and a polyimide film with a lower b* value can be obtained. The type of the inert gas at this time is not particularly limited, and can be set to argon, nitrogen, etc. In addition, in this case, the oxygen concentration is preferably less than 5 volume %, more preferably less than 3 volume %, and more preferably less than 1 volume %. The oxygen concentration in the environment is measured using a commercially available oxygen concentration meter (for example, a zirconium oxide oxygen concentration meter).

[0113] By peeling off the substrate after the imidization (closed loop) of the polyamic acid, the polyimide film is obtained. When the polyimide film is peeled off from the substrate, there is the possibility that foreign matter is adsorbed on the polyimide film due to the stripping charge. Therefore, it is preferred that (i) an antistatic agent is applied to the substrate, or (ii) an electrostatic removal member (for example, an electrostatic removal rod, an electrostatic removal wire, an ion air supply type electrostatic removal device, etc.) is provided on a coating device of polyamic acid and a stripping device of the polyimide film.

[0114] (3) Physical properties of polyimide films

[0115] The polyimide film containing the specific polyimide can be thermally pressed to various components at a relatively low temperature and has excellent transparency. Therefore, it is very useful as a protective layer, adhesive, etc. of various components. Specifically, the polyimide has the following physical properties.

[0116] (i) Glass transition temperature is 180°C or higher and 220°C or lower

[0117] (ii) Decomposition starting temperature is above 355°C

[0118] (iii) The transmittance of light with a wavelength of 400 nm is 77% or more

[0119] (iv) The b* value in the L*a*b* color system is less than 5

[0120] Hereinafter, each requirement will be described in detail.

[0121] (i) Glass transition temperature

[0122] In the polyimide film containing the above-mentioned specific polyimide, the glass transition temperature (Tg) can be set to 180°C or more and 220°C or less. The glass transition temperature (Tg) is more preferably 190°C to 210°C, and more preferably 194°C to 205°C. If the glass transition temperature of the polyimide film is 180°C or more, the heat resistance of the polyimide film when it is applied to various purposes is easy to become sufficient. On the other hand, if the glass transition temperature of the polyimide film is 220°C or less, the polyimide film can be thermocompressed to various components at a temperature of, for example, 250°C or less. In addition, if the glass transition temperature of the polyimide film is 220°C or less, even if the heating temperature when making the polyimide film is 220°C or less, the solvent is easy to fully escape from the polyimide film. Therefore, not only can the polyimide film be made at low temperatures, but the solvent is not easy to remain in the polyimide film, and the visible light transmittance is easy to become good. The glass transition temperature can be measured using a thermomechanical analyzer (TMA).

[0123] The glass transition temperature of the polyimide film is adjusted by the structure of the diamine component or the tetracarboxylic dianhydride component used to prepare the polyimide. For example, when the diamine component contains a large amount of alicyclic diamine, the glass transition temperature tends to be high, and when the diamine component contains a large amount of alkylenediamine, the glass transition temperature tends to be low. In addition, when the tetracarboxylic dianhydride component contains 4,4'-oxydiphthalic anhydride (ODPA), the glass transition temperature tends to be low.

[0124] (ii) Decomposition starting temperature

[0125] In addition, in the polyimide film including the specific polyimide, the decomposition starting temperature of the polyimide film can be set to 355° C. or higher. The decomposition starting temperature is more preferably 360° C. or higher, and further preferably 370° C. or higher. If the decomposition starting temperature of the polyimide film is 355° C. or higher, the polyimide film can be attached to various components and the like, and the polyimide film is not easily decomposed by the heat at this time.

[0126] The decomposition starting temperature of the polyimide film can be measured by a thermomechanical analyzer (TGA). In the present invention, the temperature at which the mass of 5 mg of the polyimide film decreases by 1% when the temperature is increased is defined as the decomposition starting temperature. The decomposition starting temperature of the polyimide film can be adjusted by the combination of the tetracarboxylic dianhydride component and the diamine component.

[0127] (iii) Transmittance of light with a wavelength of 400 nm

[0128] In the polyimide film containing the specific polyimide, the transmittance of light with a wavelength of 400 nm is 77% or more, preferably 80% or more, and more preferably 84% or more. If the transmittance of light with a wavelength of 400 nm of the polyimide film is 77% or more, yellowing of the polyimide film can be suppressed, and the polyimide film can be applied to applications requiring transparency, such as adhesive layers of display elements, etc.

[0129] The transmittance of the light of wavelength 400nm of the polyimide film can be determined by ultraviolet (UV)-visible spectrum measurement. In addition, the thickness of the polyimide film when measuring the transmittance is not particularly limited, and the transmittance of the polyimide film actually produced (that is, the polyimide film when the thickness is set to be used) is measured. The transmittance of the light of wavelength 400nm of the polyimide film can be adjusted by the combination of the tetracarboxylic dianhydride component and the diamine component.

[0130] (iv) b* value in the L*a*b* color system

[0131] In the polyimide film containing the specific polyimide, the b* value in the L*a*b* color system is 5 or less. The b* value is preferably 3.0 or less, and more preferably 1.0 or less. The b* value in the L*a*b* color system represents the yellowing of the polyimide film, and the smaller the value, the less yellowing. In addition, if the b* value is 5 or less, when the polyimide film is used for an adhesive layer of various displays, the adhesive layer is not easily identified.

[0132] The b* value is set to the following value: the value when the polyimide film is measured in the transmission mode using a colorimeter (for example, a tristimulus direct-reading colorimeter (Colour Cute i CC-i type) manufactured by Suga Testing Instruments). In addition, the thickness of the polyimide film when measuring the b* value is not particularly limited, and the b* value of the actually produced polyimide film (that is, the polyimide film when the thickness is set to the thickness when used) is measured.

[0133] For example, if the intrinsic viscosity (η) of the polyamic acid used to make the polyimide film is set to 0.62 dL / g or more, the b* value becomes smaller. In addition, by setting the environment when making the polyimide film to a nitrogen environment, the oxidation of the polyimide is suppressed, and the b* value tends to become lower.

[0134] (v) Thickness

[0135] The thickness of the polyimide film containing the specific polyimide is not particularly limited and can be appropriately selected according to the purpose of the polyimide film, etc. For example, when the polyimide film is used for an adhesive sheet, the thickness can be set to about 5 μm to 10 μm. On the other hand, when used as a protective layer for various components, the thickness can be set to about 10 μm to 25 μm.

[0136] (vi) Coefficient of thermal expansion (CTE)

[0137] The polyimide film containing the specific polyimide preferably has a thermal expansion coefficient of 40 to 70 ppm / K, more preferably 50 to 60 ppm / K. When the thermal expansion coefficient is within this range, expansion and contraction due to temperature changes can be reduced when the polyimide film is used for various purposes.

[0138] Regarding the thermal expansion coefficient, a polyimide film was cut into pieces with a width of 4 mm and a length of 20 mm to prepare a sample. Then, a temperature-test piece elongation curve of the sample was measured using a thermal analyzer, and the slope in the range of 60° C. to 160° C. was defined as the thermal expansion coefficient (CTE).

[0139] (vii) Haze

[0140] The haze of the polyimide film containing the specific polyimide is preferably 1.5% or less, and more preferably 1.0% or less. When the haze is within this range, the polyimide film can be easily applied to applications requiring high transparency. The haze is measured using a haze meter.

[0141] (viii) Total light transmittance

[0142] The total light transmittance of the polyimide film containing the specific polyimide is preferably 80% or more, more preferably 85% or more. If the total light transmittance is within this range, the polyimide film can be easily applied to applications requiring high transparency. The total light transmittance is measured in accordance with JIS K7105.

[0143] (ix) Retardation in the thickness direction (Rth)

[0144] The retardation (Rth) in the thickness direction per 10 μm thickness of the polyimide film containing the specific polyimide is preferably 60 or less, more preferably 50 or less. When Rth is within this range, the polyimide film can be used in optical devices and the like.

[0145] (x) Mechanical strength

[0146] The tensile strength of the polyimide film comprising the specific polyimide is preferably 100MPa or more, more preferably 110MPa or more. In addition, the tensile elongation of the polyimide film is preferably 5% or more, more preferably 20% or more. Furthermore, the tensile modulus is preferably 2.0GPa or more, more preferably 2.5GPa or more. If the tensile strength, tensile elongation, and tensile modulus are within this range, the strength of the polyimide film is sufficiently high and can be easily applied to various purposes. The tensile modulus is calculated as follows: a dumbbell-shaped punch test piece is made, and the test piece is measured under the conditions of a line width of 5mm, a sample length of 30mm, and a tensile speed of 30mm / minute using a tensile testing machine, and the stress-strain curve obtained at this time is calculated.

[0147] (4) Application of polyimide film

[0148] As described above, the polyimide film of the present invention can be formed at a relatively low temperature, for example, it can be thermocompressed at about 250° C. In addition, it has little coloration and high transparency. Therefore, it is suitable as a protective film, various adhesives, etc.

[0149] 2. Others

[0150] The polyamic acid varnish or the block polyamic acid imide varnish can also be mixed with various materials to prepare a coating liquid for forming a coating film. For example, after the coating liquid is applied to a desired substrate, the polyamic acid is imidized to obtain various coating films. At this time, the polyimide functions as an adhesive for bonding various materials to the substrate.

[0151] As described above, the glass transition temperature of the polyimide obtained by imidizing the polyamic acid or block polyamic acid imide is relatively low. Therefore, when making a coating film, it can be cured at about 220°C and is not easy to affect the substrate. In addition, since the polyimide has high transparency and high heat resistance, it can be applied to various purposes.

[0152] In addition, examples of various materials contained in the coating liquid are not particularly limited as long as they are materials such as magnetic bodies, inorganic particles, metal particles, pigments, dyes, etc. that do not impair the purpose of the present invention.

[0153] In addition, the coating method, heating method, etc. of the coating liquid when forming the coating film may be the same as the coating method or heating method of the varnish.

[0154] Example

[0155] Hereinafter, the present invention will be described in more detail by way of examples, but the scope of the present invention is not limited by these examples.

[0156] 1. Tetracarboxylic dianhydride component and diamine component

[0157] The abbreviations of the tetracarboxylic dianhydride component and the diamine component used in Examples and Comparative Examples are as follows, respectively.

[0158] [Tetracarboxylic dianhydride component]

[0159] ODPA: 4,4'-oxydiphthalic anhydride

[0160] s-BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride

[0161] [Diamine component]

[0162] 1,4-BAC: 1,4-bis(aminomethyl)cyclohexane

[0163] HMDA: 1,6-hexanediamine

[0164] 1. Preparation of polyamic acid varnish

[0165] (Synthesis example 1)

[0166] In a flask equipped with a thermometer, a condenser, a nitrogen inlet tube and a stirring blade, 1,4-BAC: 7.11g (0.050 mol), HMDA: 5.81g (0.050 mol) and N-methyl-2-pyrrolidone (NMP): 193.0g were added and stirred under a nitrogen atmosphere to form a uniform solution. Thereafter, the mixture was cooled to 15°C, s-BPDA: 26.3g (0.090 mol) and ODPA: 3.10g (0.010 mol) were added in powder form and stirred directly. After about 1 hour, heat gradually occurred and an increase in viscosity was observed. The mixture was heated and reacted at an internal temperature of 60°C to 70°C for 1 hour, resulting in a uniform solution. Thereafter, the mixture was cooled to room temperature and aged overnight at room temperature to obtain a light yellow viscous varnish. The intrinsic viscosity (η) of the obtained polyamic acid varnish (polymer concentration 0.5 g / dL, NMP, measured with an Ubbelohde viscometer at 25°C) was 1.18 dL / g, and the viscosity at 25°C measured with an E-type viscometer was 12,200 mPa·s. Table 1 shows the composition and physical properties of the obtained polyamic acid.

[0167] (Synthesis example 2)

[0168] In the same reaction apparatus as in Synthesis Example 1, 1,4-BAC: 7.11 g (0.050 mol), HMDA: 5.81 g (0.050 mol) and N-methyl-2-pyrrolidone (NMP): 192.2 g were added, and stirred under a nitrogen atmosphere to form a uniform solution. Thereafter, the mixture was cooled to 15°C, and s-BPDA: 29.28 g (0.10 mol) was added thereto in powder form, and stirred directly. After about 1 hour, the mixture gradually heated up, and an increase in viscosity was found. The mixture was heated up, and reacted at an internal temperature of 60°C to 70°C for 1 hour, resulting in a uniform solution. Thereafter, the mixture was cooled to room temperature, and aged overnight at room temperature to obtain a light yellow viscous varnish. The intrinsic viscosity (η) of the obtained polyamic acid varnish (polymer concentration 0.5 g / dL, NMP, measured with an Ubbelohde viscometer at 25°C) was 1.00 dL / g, and the viscosity at 25°C measured with an E-type viscometer was 28,400 mPa·s. Table 1 shows the composition and physical properties of the obtained polyamic acid.

[0169] (Synthesis example 3)

[0170] In the same reaction apparatus as in Synthesis Example 1, 8.53 g (0.060 mol) of 1,4-BAC, 4.65 g (0.040 mol) of HMDA and 194.1 g of N-methyl-2-pyrrolidone (NMP) were added, and stirred under a nitrogen atmosphere to prepare a uniform solution. Thereafter, the mixture was cooled to 15°C, and 26.33 g (0.090 mol) of s-BPDA and 3.10 g (0.010 mol) of ODPA were added thereto in powder form, and stirred directly. After about 1 hour, the mixture gradually heated up, and an increase in viscosity was found. The mixture was heated up, and reacted at an internal temperature of 60°C to 70°C for 1 hour, resulting in a uniform solution. Thereafter, the mixture was cooled to room temperature, aged overnight at room temperature, and a light yellow viscous varnish was obtained. The intrinsic viscosity (η) of the obtained polyamic acid varnish (polymer concentration 0.5 g / dL, NMP, measured with an Ubbelohde viscometer at 25°C) was 0.77 dL / g, and the viscosity at 25°C measured with an E-type viscometer was 6,300 mPa·s. Table 1 shows the composition and physical properties of the obtained polyamic acid.

[0171] (Synthesis Example 4)

[0172] In the same reaction apparatus as in Synthesis Example 1, 1,4-BAC: 9.96 g (0.070 mol), HMDA: 3.49 g (0.030 mol) and N-methyl-2-pyrrolidone (NMP): 193.0 g were added, and stirred under a nitrogen atmosphere to form a uniform solution. Thereafter, the mixture was cooled to 15°C, and s-BPDA: 26.33 g (0.090 mol) and ODPA: 3.10 g (0.010 mol) were added thereto in powder form, and stirred directly. After about 1 hour, heat gradually occurred, and an increase in viscosity was found. The mixture was heated and reacted at an internal temperature of 60°C to 70°C for 1 hour, resulting in a uniform solution. Thereafter, the mixture was cooled to room temperature, aged overnight at room temperature, and a light yellow viscous varnish was obtained. The intrinsic viscosity (η) of the obtained polyamic acid varnish (polymer concentration 0.5 g / dL, NMP, measured with an Ubbelohde viscometer at 25°C) was 1.14 dL / g, and the viscosity at 25°C measured with an E-type viscometer was 53,800 mPa·s. Table 1 shows the composition and physical properties of the obtained polyamic acid.

[0173] (Synthesis Example 5)

[0174] In the same reaction apparatus as in Synthesis Example 1, 7.11 g (0.050 mol) of 1,4-BAC, 5.81 g (0.050 mol) of HMDA and 194.4 g of N-methyl-2-pyrrolidone (NMP) were added, and stirred under a nitrogen atmosphere to prepare a uniform solution. Thereafter, the mixture was cooled to 15°C, and 20.45 g (0.070 mol) of s-BPDA and 9.31 g (0.030 mol) of ODPA were added in powder form, and stirred directly. After about 1 hour, the mixture gradually heated up, and the viscosity was found to increase. The mixture was heated up, and reacted at an internal temperature of 60°C to 70°C for 1 hour, resulting in a uniform solution. Thereafter, the mixture was cooled to room temperature, aged overnight at room temperature, and a light yellow viscous varnish was obtained. The intrinsic viscosity (η) of the obtained polyamic acid varnish (polymer concentration 0.5 g / dL, NMP, measured with an Ubbelohde viscometer at 25°C) was 1.15 dL / g, and the viscosity at 25°C measured with an E-type viscometer was 53,800 mPa·s. Table 1 shows the composition and physical properties of the obtained polyamic acid.

[0175] (Comparative Synthesis Example 1)

[0176] In the same reaction apparatus as in Synthesis Example 1, 7.11 g (0.050 mol) of 1,4-BAC, 5.81 g (0.050 mol) of HMDA and 195.9 g of N-methyl-2-pyrrolidone (NMP) were added, and stirred under a nitrogen atmosphere to prepare a uniform solution. Thereafter, the mixture was cooled to 15°C, and 14.56 g (0.050 mol) of s-BPDA and 15.51 g (0.050 mol) of ODPA were added thereto in powder form, and stirred directly. After about 1 hour, the mixture gradually heated up, and an increase in viscosity was found. The mixture was heated up, and reacted at an internal temperature of 60°C to 70°C for 1 hour, resulting in a uniform solution. Thereafter, the mixture was cooled to room temperature, aged overnight at room temperature, and a light yellow viscous varnish was obtained. The intrinsic viscosity (η) of the obtained polyamic acid varnish (polymer concentration 0.5 g / dL, NMP, measured with an Ubbelohde viscometer at 25°C) was 0.73 dL / g, and the viscosity at 25°C measured with an E-type viscometer was 5,700 mPa·s. Table 1 shows the composition and physical properties of the obtained polyamic acid.

[0177] [Table 1]

[0178]

[0179] 2. Preparation of polyimide film

[0180] (Example 1)

[0181] The polyamic acid varnish prepared in Synthesis Example 1 is applied to a glass substrate using a doctor blade to form a coating of polyamic acid varnish. The laminate comprising a substrate and a coating of polyamic acid varnish is placed in an inactive oven. Thereafter, the oxygen concentration in the inactive oven is controlled to be less than 0.1% by volume, and the environment in the oven is heated from 50°C to 220°C (heating rate: 2°C / min) for 85 minutes, and then maintained at 220°C for 2 hours. After the heating is completed, it is naturally cooled in an inactive environment. Thereafter, the sample is immersed in distilled water and the polyimide film is peeled off from the substrate. The thickness and various physical properties of the polyimide film obtained are shown in Table 2.

[0182] (Examples 2 to 5, and Comparative Example 1)

[0183] A polyimide film was produced in the same manner as in Example 1 except that the polyamic acid varnish was changed to the polyamic acid varnish shown in Table 2. Table 2 shows the thickness and various physical properties of the obtained polyimide film.

[0184] (Example 6)

[0185] The polyamic acid varnish prepared in Synthesis Example 1 is applied to a glass substrate using a scraper blade to form a coating of polyamic acid varnish. The laminate comprising a substrate and a coating of polyamic acid varnish is placed in an oven under an air environment. Thereafter, the environment in the oven is heated from 50 ° C to 220 ° C (heating rate: 2 ° C / min) over 85 minutes, and then maintained at 220 ° C for 2 hours. After the heating is completed, it is naturally cooled in an inactive environment. Thereafter, the sample is immersed in distilled water and the polyimide film is peeled off from the substrate. The thickness and various physical properties of the obtained polyimide film are shown in Table 2.

[0186] [Example 7 to Example 10]

[0187] A polyimide film was produced in the same manner as in Example 6 except that the polyamic acid varnish was changed to the polyamic acid varnish shown in Table 2. Table 2 shows the thickness and various physical properties of the obtained polyimide film.

[0188] 3. Evaluation

[0189] The polyimide films produced in Examples and Comparative Examples were evaluated by the following methods.

[0190] 1) Determination of glass transition temperature (Tg)

[0191] The polyimide films produced in Examples and Comparative Examples were cut into pieces having a width of 4 mm and a length of 20 mm. The glass transition temperature (Tg) of the samples was measured using a thermal analyzer (TMA-50) manufactured by Shimadzu Corporation.

[0192] 2) Determination of decomposition starting temperature (Td1)

[0193] 5 mg of the polyimide film produced in Examples and Comparative Examples was weighed and the sample was heated at 10°C / min using a thermal analyzer (TGA-60) manufactured by Shimadzu Corporation to measure the decomposition starting temperature. The decomposition starting temperature was the temperature at which the mass decreased by 1%.

[0194] 3) Light transmittance measurement

[0195] The polyimide films produced in Examples and Comparative Examples were subjected to UV-visible spectrum measurement in the wavelength range of 300 nm to 800 nm using Multi Spec-1500 manufactured by Shimadzu Corporation to obtain the transmittance of light at a wavelength of 400 nm.

[0196] 4) b* value determination

[0197] The polyimide films prepared in Examples and Comparative Examples were measured for b* values, which are an index of yellow hue of the polyimide films, in a transmission mode using a tristimulus direct-reading colorimeter (Colour Cute i CC-i model) manufactured by Suga Test Instruments.

[0198] 5) Coefficient of Thermal Expansion (CTE)

[0199] The polyimide films prepared in the examples and comparative examples were cut into pieces with a width of 4 mm and a length of 20 mm. The temperature-test piece elongation curve of the sample was measured using a thermal analyzer (TMA-50) manufactured by Shimadzu Corporation, and the slope in the range of 60°C to 160°C was defined as the coefficient of thermal expansion (CTE).

[0200] 6) Haze

[0201] The haze of the polyimide films produced in Examples and Comparative Examples was measured using a haze meter (NDH2000) manufactured by Nippon Denshoku Industries.

[0202] 7) Total light transmittance

[0203] The total light transmittance of the polyimide films produced in Examples and Comparative Examples was measured in accordance with JIS K7105.

[0204] 8) Retardation in the thickness direction per 10 μm thickness (Rth)

[0205] The phase difference in the thickness direction of the polyimide film was measured at a wavelength of 633 nm using a prism coupler (2010 model, manufactured by Metricon Corporation), and the obtained value was converted into a value per 10 μm thickness (Rth).

[0206] 9) Tensile strength, tensile elastic modulus and tensile elongation

[0207] Make dumbbell type punching test piece, utilize tensile testing machine (manufactured by Shimadzu Corporation, EZ-S), measure under the condition of line width 5mm, sample length 30mm, tensile speed 30mm / minute.According to the stress-strain curve obtained, the intensity and elongation of the point reaching fracture are set as tensile strength and tensile elongation respectively.In addition, these are the average values ​​of the measured values ​​of 5 times respectively.In addition, tensile elastic modulus is obtained according to stress-strain curve.

[0208] [Table 2]

[0209]

[0210] As shown in Table 2 above, when it is a polymer of a tetracarboxylic dianhydride component and a diamine component, and the tetracarboxylic dianhydride component contains 60 mol% to 100 mol% of 4,4'-oxydiphthalic anhydride (BPDA) relative to its total amount, and the diamine component contains 30 mol% to 70 mol% of alicyclic diamine and 30 mol% to 70 mol% of alkylenediamine relative to its total amount, the intrinsic viscosity η of the polyamic acid reaches 0.62 dL / g or more (Examples 1 to 10). In addition, the glass transition temperature of the polyimide film obtained from this polyamic acid is above 180°C and below 220°C, the decomposition starting temperature is above 355°C, the transmittance of light with a wavelength of 400nm is above 77%, and the b* value in the L*a*b* colorimetric system is below 5. Therefore, these polyimide films can be used in various applications. In addition, since Tg is in the above range, it can be hot-pressed at, for example, about 250°C.

[0211] In addition, if a general polyimide is imidized in an air environment, the polyimide is easily colored or the light transmittance is easily greatly reduced. In contrast, even if the polyimide of the above examples is imidized in an air environment, the light transmittance is not excessively reduced and it is not easy to be colored (Examples 6 to 10).

[0212] On the other hand, in Comparative Example 1 in which the amount of 4,4′-oxydiphthalic anhydride (BPDA) was less than 60 mol % based on the total amount of the tetracarboxylic dianhydride component, the transmittance was low.

[0213] This application claims priority based on Japanese Patent Application No. 2019-182840 filed on October 3, 2019. All the contents described in these application specifications are incorporated herein by reference.

[0214] Industrial Applicability

[0215] The polyimide film of the present invention can be formed at a relatively low temperature, for example, it can be thermocompressed at about 250° C. In addition, it has little coloration and high transparency. Therefore, it can be used in adhesive layers, protective layers, etc. of various display elements.

Claims

1. A polyimide film comprising a polyimide which is a polymer of a tetracarboxylic dianhydride component and a diamine component, The glass transition temperature is 180°C or higher and 220°C or lower. The tetracarboxylic dianhydride component includes 60 mol% to 100 mol% of biphenyltetracarboxylic dianhydride relative to the total amount of the tetracarboxylic dianhydride, and the biphenyltetracarboxylic dianhydride may have three or less substituents including an alkyl group having 1 to 4 carbon atoms, The diamine component contains 30 mol % to 70 mol % of an alicyclic diamine and 30 mol % to 70 mol % of an alkylene diamine, based on the total amount of the diamine component. 2 . The polyimide film according to claim 1 , wherein a molar ratio of the alicyclic diamine to the alkylenediamine in the diamine component is 4 / 6 or more and 6 / 4 or less. 3 . The polyimide film according to claim 1 , wherein the alkylene group of the alkylenediamine has 2 to 12 carbon atoms. The polyimide film according to claim 1 , wherein the alicyclic diamine is at least one compound selected from the group consisting of 1,4-diaminomethylcyclohexane, 1,3-diaminomethylcyclohexane, norbornanediamine, cyclohexanediamine, isophoronediamine, and 4,4′-methylenebis(cyclohexylamine). The polyimide film according to claim 1 , wherein the alicyclic diamine comprises 1,4-diaminomethylcyclohexane, and the alkylenediamine comprises 1,6-hexamethylenediamine. 6 . The polyimide film according to claim 1 , wherein the tetracarboxylic dianhydride component contains 40 mol % or less of 4,4′-oxydiphthalic anhydride. 7 . A polyimide laminate comprising: a substrate and the polyimide film according to claim 1 disposed on the substrate.